Axial compression performance of thin-walled T-shaped concrete filled steel tubular columns under constant high temperature: Experimental and numerical study. (October 2020) - Wang, Weiwei; Lyu, Xuetao; Zhang, Yuzhuo; Yu, Yang; Zhang, Tong
Highlights: T-shaped CFST stub columns exposed to elevated temperature were investigated. Axial compression tests on eight specimens were conducted at elevated temperature. FE models were developed to study the specimen behaviour. Design formulae were proposed to calculate the load-bearing capacity. Abstract: This study investigates the effects of temperature and stiffener on the axial compression performance of thin-walled T-shaped concrete filled steel tubular (CFST) stub columns. Eight CFST columns with and without stiffener were fabricated and exposed to different elevated temperatures, then tested for axial compressive performance. The complete load-displacement curve of the specimens under axial compression, the failure pattern after test and the failure characteristics of concrete core are also discussed. The finite element analysis is then developed to establish the calculation model of temperature field and axial pressure field of thin-walled T-shaped concrete filled steel tubular stub columns with stiffeners at constant high temperature. The FE model presents a highly agreement with experimental data in term of load-displacement behavior, which enable to further investigate stress distribution and failure mechanism of the columns. In addition, parametric study is conducted showing that temperature, thickness of steel tube, yield strength of steel tube and compressive strength of concrete are the key factors in contributing to axial compressive performance of the CFST stub columns. Finally, to provide reference for practical application of engineering, a simplified calculation formula for ultimate bearing capacity and axial compression stiffness of CFST stub columns were obtained via the regression analysis based on results from the experimental and numerical analysis. The result shows that the relative errors between results calculated from simplified formulae and from FE models are within 10%, which indicates that the proposed formulae are able to provide the theoretical reference for the practical engineering applications.